2015
DOI: 10.1002/ejp.640
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical model of hyperalgesia following spinal stenosis/compression

Abstract: Histology revealed that hyperalgesia occurred when there was: (1) damage to spinal white matter; or (2) cystic cavitation; or (3) compression and distortion of the spinal cord without an obvious loss of grey or white matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Rats with severe T3 SCI also consistently developed forelimb tactile allodynia, which was reversed by gabapentin, and increased sensitivity to cold, both of which have been reported by patients with "at-level" pain [26]. "At-level" cold allodynia has previously been reported in a model of photochemically-induced ischemic injury [27], while conscious aversion to cold flooring has been reported in a rat model of spinal stenosis [53]. Acute "at-level" cold sensitivity to acetone has also been reported following T9 complete transection [41].…”
Section: ]mentioning
confidence: 71%
“…Rats with severe T3 SCI also consistently developed forelimb tactile allodynia, which was reversed by gabapentin, and increased sensitivity to cold, both of which have been reported by patients with "at-level" pain [26]. "At-level" cold allodynia has previously been reported in a model of photochemically-induced ischemic injury [27], while conscious aversion to cold flooring has been reported in a rat model of spinal stenosis [53]. Acute "at-level" cold sensitivity to acetone has also been reported following T9 complete transection [41].…”
Section: ]mentioning
confidence: 71%
“…An alternate version of the task avoids this problem by warming or cooling the entire floor in the dark side of the chamber. This variant of PEAP has shown that rats with T13 hemisection have reduced sensitivity to noxious heat [39], but those with a spinal stenosis show increased sensitivity to cold and heat [43]. However, this too can be an imperfect approach as only the paws are contact with the stimulus surface, precluding evaluation of at-level pain in the flanks.…”
Section: Evaluating Conscious Perception Of Pain In Sci Modelsmentioning
confidence: 99%
“…In a similar dual-chamber PEAP paradigm the mechanical stimulation is replaced by thermal stimulation to assess cold and/ or heat sensitivity [28,35]. In the dark chamber hot, cold or neutral thermal stimuli are applied through a temperature regulated floor plate.…”
Section: 1 Behavioral Assessmentsmentioning
confidence: 99%
“…In this paradigm animals are trained to establish stimulus preference between avoidance of thermal stimulation and bright light [29]. In a model of low thoracic spinal cord compression Vierck et al were able to measure cold and hot hyperalgesia in SCI [35]. …”
Section: 1 Behavioral Assessmentsmentioning
confidence: 99%